Level of Acceptance of Illness and Its Association with Quality of Life among Patients with Epilepsy in North Shewa, Ethiopia - Yonas Teshome; Yerukneh Solomon; Feredegn Talargia; Negese Worku; Abreham Shitaw; Abebaye Aragaw Leminie (Behavioural Neurology)
Acceptance of illness is regarded as an indicator of functioning and predictor of quality of life. However, quality of life of patients with epilepsy in sub-Saharan countries worsen because of low medication adherence, increased morbidity and mortality, and the stigmatization associated with the disease. This research is aimed at assessing the level of acceptance of illness of patients with epilepsy and associated quality of life in North-East Ethiopia. Methods. A cross-sectional study was conducted from January to June 2021 at the Debre Berhan Referral Hospital, North-East Ethiopia. A total of 78 patients with epilepsy aged more than 18 years were randomly selected and assessed using Quality of Life in Epilepsy Inventory 31 and acceptance of illness scale. In addition, authors owned questionnaire were used to evaluate the sociodemographic and clinical characteristics of the patients. P value < 0.05 at 95% confidence level was considered to be statistically significant in all the analysis. Result. The study participants’ age varied between 18 and 67 years with the mean age of 28.9 years. Phenobarbital was the most used (73.9%) antiepileptic drug, and 68.7% (n=66) of the patients seizure was controlled. 72.9% (n=70) of the patients had medium acceptance of illness (scored 20-30), while 17.7% (n=17) had low illness acceptance level (scored 8-19), and 9.4% (n=9) had high acceptance of illness (scored 31-40). The mean of overall acceptance of illness among epileptic patients was 21.04±7.21. The overall score of QOLIE-31 was 79.14±25.46, and the highest mean score was for cognitive (83.5±27.1), while the lowest mean score was that of medication effect (72.7±28.7). Five of the seven QOLIE-31 components correlated significantly with level of acceptance of illness. Cognitive domain (r=0.498, p<0.001) demonstrated the highest correlation followed by overall quality of life (r=0.489, p<0.001), seizure worry (r=0.433, p<0.001), energy/fatigue (r=0.342, p<0.001), and emotional well-being (r=0.278, p<0.001). Conclusion. Patients with epilepsy in the study area had medium acceptance of illness, and nearly half of them had mean and more than the mean quality of life. The patients’ acceptance of illness was significantly associated with overall quality of life, seizure worry, emotional well-being, and cognitive domain of the patients.